Modern Challenges to Traditional Justice: The Struggle to Deliver Remedy and Reparation in War-Affected Lango (Tufts Archival Research Center, 2018)
Modern Challenges to Traditional Justice: The Struggle to Deliver Remedy and Reparation in War-Affected Lango, by Teddy Atim and Keith Proctor